2021
DOI: 10.1111/ipd.12929
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of various herbal extracts on biofilms of Streptococcus mutans and Scardovia wiggsiae: An in vitro study

Abstract: Background Owing to their strong antimicrobial properties, Helichrysum arenarium (HA), Anzer thyme (AT), and Stevia rebaudiana (SR) have been commonly used in medicine. Aim This study aimed to evaluate antimicrobial activities of HA, AT, and SR against S. mutans and S. wiggsiae in biofilms formed on primary teeth. Design Fifty enamel samples were divided into two groups: mono‐species biofilm and two‐species biofilm. Each biofilm group was divided into five subgroups (n = 5): group 1, HA; group 2, AT; group 3, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
0
0
Order By: Relevance
“…The extract itself showed similar antibacterial effects against methicillin-resistant S. aureus and penicillin-resistant clinical isolates of S. pneumoniae, showing higher activity against the ampicillin-resistant isolate Moraxella catarrhalis (Gradinaru et al, 2014). of H. arenarium has pronounced antibacterial properties against cariogenic bacteria, such as Streptococcus mutans (Demirez Bircan et al, 2022). Kutluk et al (2018) showed antibacterial, antifungal and antiviral activity of extracts obtained from seven species of the Helichrysum genus.…”
Section: Introductionmentioning
confidence: 94%
“…The extract itself showed similar antibacterial effects against methicillin-resistant S. aureus and penicillin-resistant clinical isolates of S. pneumoniae, showing higher activity against the ampicillin-resistant isolate Moraxella catarrhalis (Gradinaru et al, 2014). of H. arenarium has pronounced antibacterial properties against cariogenic bacteria, such as Streptococcus mutans (Demirez Bircan et al, 2022). Kutluk et al (2018) showed antibacterial, antifungal and antiviral activity of extracts obtained from seven species of the Helichrysum genus.…”
Section: Introductionmentioning
confidence: 94%